FACTORS ASSOCIATED WITH THE INCIDENCE OF HYPOTENSION IN PATIENTS UNDER CAESAREAN SECTION WITH SPINAL ANESTHESIA AT MUHAMMADIYAH HOSPITAL, PALEMBANG - Joko Murdiyanto; Heri Puspito; Tiara Putri Dela (Journal of Indonesian Anesthesiology Nursing, 2026)
ABSTRACT Background: Hypotension can possibly occur when systolic blood pressure drops below 90 mmHg and diastolic blood pressure falls below 60 mmHg. The sympathetic nervous system, which controls vascular muscle tone, is blocked during spinal anesthesia, resulting in hypotension Methods: This is a quantitative study using an analytical observational method. The study was conducted from February to March 2026 at the Central Operating Theater (COT) of Muhammadiyah Hospital, Palembang. The sample size was 40 respondents that met the inclusion and exclusion criteria. Chisquare analysis was performed in this study. Results: Two variables were significantly associated with the incidence of hypotension in cesarean section patients with spinal anesthesia: age (p-value = 0.046) and the level of sympathetic blockade (p-value = 0.033). The variables of anesthetic drug type and body position did not show a significant association with the incidence of hypotension (p-value = 0.364) and (p-value = 0.673). Conclusion: There is a significant association between age and the level of sympathetic blockade and the incidence of hypotension in cesarean section patients with spinal anesthesia at the Muhammadiyah Hospital, Palembang. Variables that did not show a significant association with the incidence of hypotension were anesthetic drug type and body position.